UJI KEDAP SUARA PUING BATA DAUR ULANG SEBAGAI ALTERNATIF MATERIAL BERKELANJUTAN - Hendrico Firzandy Latupeirissa; Gierlang Bhakti Putra; Niki Prastomo (Universitas Multimedia Nusantara, 2020)
Brick debris that makes up the majority of construction waste has not received proper waste disposal in Indonesia. On the other hand, brick debris could be potentially reused as non-structural building materials to reduce its negative impact on the environment. This study aims to test the effectiveness of soundproofing on recycled brick debris. The soundproof test was carried out on brick debris in the form of fine and coarse grains. The simulation box is then used as a support for the brickwork material and then the box is exposed to a sound source with a certain level of noise that is considered disturbing human comfort. Noise level measurements are made in the outside and inside the box. These measurements are tabulated and then analyzed to see the success of the two aggregates in reducing noise. Basically, the brickwork material has succeeded in becoming a recycled building material that can absorb noise, although further research must be carried out to be able to state that this material is truly ready to be used as an alternative building material with good acoustic capabilities.